Reaksi Pasar Perusahaan LQ 45 pada Masa Pandemi COVID-19 di Bursa Efek Indonesia - Jaya Kusuma, Putu Sri Arta (E-Jurnal Akuntansi; Vol 32 No 6 (2022), 2022)
The stock market usually reacts to an event both economic and non-economic events such as the COVID-19 pandemic. The aim of the study is to test whether there is a market reaction to key events during the COVID-19 pandemic. The research was conducted on LQ45 companies, which are companies that have the largest market capitalization and are the most liquid companies on the Indonesia Stock Exchange. The analysis technique used is one sample t-test. The test is carried out by analyzing whether there are abnormal returns after important events during the COVID-19 pandemic. Based on the research results, it is known that investors responded negatively to the announcement of the first COVID-19 patient in Indonesia and the announcement of large-scale social restrictions (PSBB) but did not respond to the announcement of the new normal era. The positive market response was shown at the start of the COVID-19 vaccination program. Keywords: COVID-19; Abnormal Return; LQ45